The effect of leadership on internationalization performances : A case study of Czech based company. - Scali, Mattia; Srivastava, Mohit; Petrů, Jaroslav; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2020)
The study aims to understand the relationship between leadership style and internationalization and see the impact it has on the performance of a Czech based company. To do it a survey was structured and fulfilled by one hundred and ten respondents. The data were analyzed thanks to the use of the statistical tool SPSS 25 and AMOS 26. To study the adequacy of the sample EFA and CFA analysis were conducted. A PMCC was conducted to address the linear relation between the key variables of this study: leadership style, performance, entrepreneurial orientation, domestic learning effort, and international learning effort. Then to study the variability in one dependent variable due to leadership style a regression coefficient was calculated. The last point was the study of the moderating effect of entrepreneurial orientation. The results show a positive effect of leadership style on the international performance of Czech based company.
Vedoucí práce: Mohit Srivastava
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses